Arduino-based Automatic Control System for Turn Signal and Brake Lights on Motorcycle - Warsono Putra; Wawan Purwanto; Aulia Fajrin Rahmadani Nasution (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
The number of motorcycles circulating on Indonesian roads in 2018 reached 111,470,878 units. With this amount of traffic on the highway becomes congested and potentially high accidents. One of the factors causing the accident is the motorcycle rider's negligence in using turn signal and brake lights. This study aims to make a tool that works automatically to control the active and inactive brake lights and turn signal on a motorcycle. This tool was successfully developed and implemented using an arduino microcontroller and controller information was taken from the Throttle Position Sensor, Speed sensor, turn signal and brake light control switches. Jumlah sepeda motor yang beredar di jalan raya Indonesia pada 2018 mencapai 111.470.878 unit. Dengan jumlah ini lalu lintas di jalan raya menjadi padat dan rawan akan kecelakaan. Salah satu faktor penyebab kecelakaan adalah kelalaian pengendara sepeda motor dalam menggunakan lampu sein dan lampu rem. Penelitian ini bertujuan untuk membuat sebuah alat yang bekerja secara otomatis untuk mengatur hidup dan matinya lampu rem dan lampu sein pada sepeda motor. Alat ini berhasil dikembangkan dan diimplementasikan dengan menggunakan mikrokontroler arduino dan informasi dari sensor seperti Throttle Position Sensor, Speed sensor, saklar lampu sein dan rem.